A glimpse of fear: Fast detection of threatening targets in visual search with brief stimulus durations. Issue 1 (12th March 2013) - Soares, Sandra C.; Esteves, Francisco
Abstract Reliable detection of a threat based on temporally restricted information allows organisms to activate their defensive mechanisms. In the present study we investigated attentional efficiency for prototypical evolutionarily relevant stimuli, snakes (compared with spiders and mushrooms), during visual search conditions in which displays were presented for brief durations and under conditions of high perceptual load. Participants were exposed to a visual search paradigm in which the duration of the display varied between 150 and 300 ms. Perceptual load was manipulated using small, medium, and larger displays (4, 6, and 8 items, respectively). The results showed that fear stimuli, compared with neutral stimuli, were more accurately and quickly detected under both visually degraded conditions. The results also showed differences between the two categories of fear‐relevant stimuli (snakes and spiders) in their dependency on perceptual load manipulations. Snake targets were overall detected more accurately than spiders, with this snake advantage effect being more clear‐cut with many distracters (high load) than with few (low load). The results were interpreted in light of an evolutionary‐based theory (the snake detection theory), which posits that snakes are the prototypical predators of primates.